1972
DOI: 10.1073/pnas.69.4.809
|View full text |Cite
|
Sign up to set email alerts
|

Nonprotein Amino Acids from Spark Discharges and Their Comparison with the Murchison Meteorite Amino Acids

Abstract: All the nonprotein amino acids found in the Murchison meteorite are products of the action of electric discharge on a mixture of methane, nitrogen, and water with traces of ammonia. These amino acids include a-amino-n-butyric acid, a-aminoisobutyric acid, norvaline, isovaline, pipecolic acid, fl-alanine, 6-amino-n-butyric acid, j#-aminoisobutyric acid, -y-aminobutyric acid, sarcosine, N-ethylglycine, and N-methylalanine. In addition, norleucine, alloisoleucine, N-propylglycine, N-isopropyl-glycine, N-methyl-ft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
110
0
5

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(120 citation statements)
references
References 14 publications
5
110
0
5
Order By: Relevance
“…Accordingly, we examined the reaction of 2-aminothiazole (7) with aldehydes and ketones 2d-w, which are all prebiotic amino acid precursors. 2,[8][9][10][11][12][13] All of the aldehydes furnished their aminals (8d-w) in excellent yield (Table 1). In stark contrast, no ketone aminals precipitated, even after extended incubation.…”
Section: Selective Synthesis Of Pentose Aminooxazoline (1) From a Commentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, we examined the reaction of 2-aminothiazole (7) with aldehydes and ketones 2d-w, which are all prebiotic amino acid precursors. 2,[8][9][10][11][12][13] All of the aldehydes furnished their aminals (8d-w) in excellent yield (Table 1). In stark contrast, no ketone aminals precipitated, even after extended incubation.…”
Section: Selective Synthesis Of Pentose Aminooxazoline (1) From a Commentioning
confidence: 99%
“…[8][9][10][11][12][13] Thus, to investigate 2-aminothiazole (7) induced selective amino acid synthesis, a mixture of eight prebiotic aldehydes and ketones 2 (Fig. 5) was incubated with 2-aminothiazole (7; 10 equiv.…”
Section: Selective Synthesis Of Pentose Aminooxazoline (1) From a Commentioning
confidence: 99%
See 2 more Smart Citations
“…DHUR has been found in the urine of rats and is excreted quantitatively (Toppet aL, 1993 The half-life of ring opening of 9 h at 100°C is not that rapid compared to the optimum doubling time of hyperthermophiles, which is i-3 h (Pley et al, 1991;Kurr et al, 1991;Vrlkl et al, 1993 (Wolman et al, 1972) and are also found in the Murchison meteorite (Kvenvolden et ai., 1971;Peltzer et aLo 1984). Small amounts of hydantoic acids and hydantoins have also been found in the Murchison meteorite (Cooper & Cronin, 1995).…”
Section: In Vivo Stabili_ Of Dihydrouridinementioning
confidence: 99%